Safety and efficacy of fumonisin esterase from Komagataella phaffii DSM 32159 as a feed additive for all animal species. (20th July 2020) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kos Durjava, Mojca; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of fumonisin esterase from Komagataella phaffii DSM 32159 as a technological feed additive for all animal species. The product has been already assessed by the FEEDAP Panel for use in pigs and poultry feed as technological additive and was granted with an authorisation in the EU for this use. In the current application, the additive is intended to be used in fermenting feeds with the purpose to reduce the contamination of feed by fumonisins. New data provided showed that no recombinant DNA could be detected in three batches of the product. The evidence provided – based on the data submitted in the previous and the current application – allowed the FEEDAP Panel to conclude that the additive is safe for the target animals under the proposed conditions of use. The Panel also considered valid the previous conclusions in which the safety of the additive for consumers and the environment was established. The additive is not toxic by inhalation and the respiratory exposure is likely to be low; however, a risk of sensitisation via the respiratory route cannot be excluded. The additive is non‐irritant to skin and eyes and is not considered as a dermal sensitiser. The additive has the capacity to degrade fumonisins in fermenting feed (with a fumonisin content within the guidance limits operating in the EU) when used at the minimum recommended dose of 40 U/kg feed. The FEEDAP Panel notes that the efficacy has been demonstrated only in silages, not in other fermenting feeds like e.g. liquid feeds.